Designing a Research Proposal for Construction Materials Health Management (CMHM) System - Redmond, Alan Martin; Fies, Bruno; Zarli, Alain (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
This papers problem statement relates to IAQ and thesharp rise in the number of people diagnosed with allergicdiseases in developed countries. The issues ofcustomizing homes for health needs of their occupantsrequires proofing against allergens caused by materials orproducts. In order, to use ICT applications systems foridentifying/analyzing materials between customers andsuppliers, an inter-organizational system is required.However, such a process has limitations due todependencies on different data structures between allinterfaces and an external system. The papersmethodology is based on purposing ‘CRM - BI - SCM’interface system that will ensure compatibility betweensystem segments and components of CMHM system. Thesystem architecture features; i) knowledge-based supportsystem (TOPIS method) for evaluation of hazardousmaterial selection; ii) linking BIM (Building InformationModel) model components with a materials selection thatnot only prompts the cost per unit but also predicts thepotential hazards associated with this decision; and iii)OWL-S specification for atomic process focusing onsemantic match making. The proposal presents aninterface based on Cloud BIM platform as an integratedinformation system that links material components thatare tagged to health documents extracted from a BIMmodel in order to provide an online supply Network of thewhole Business Process.